Penerapan Etika Bisnis Syariah dalam Bisnis UMKM (Studi Kasus Roemah Burger Bagan Deli) - Siti Afifah Salsabila; Novien Rialdy (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the sharia business ethics applied by the owners of Micro, Small and Medium Enterprises (MSMEs) Roemah Burger using a qualitative approach, this study collected data through in-depth interviews and observations at MSME Roemah Burger. MSME Roemah Burger itself is a business engaged in the culinary field such as burgers, kebabs, toast, roti canai and pempek. The results of the analysis show that ethics in a business are very important because this is the main foundation in running a business where buyers will feel satisfied with the ethics applied by the seller where the application of this ethics is increasingly relevant to create sustainable competitiveness and increase customer trust. This ethic does not only cover the attitude of the seller but also the condition of a product being marketed whether it is as claimed or exaggerated. This is very important to apply in every business so that the business gets the satisfaction desired by buyers and will become loyal customers, this can also increase profits in a business. Islam itself permits buying and selling as long as it is in accordance with the principles of the Islamic religion